John"s gospel and the Johannine church: A mirror of events wifhin a text or/and a window on events within a church - Lombard, H. A. (Hervormde teologiese studies, 1987)
This paper investigates the problem of an alleged Johannine church/ school. The hermeneutical paradigms and results of two mainline exegetical methods are assessed, namely the historico-critical method and literary criticism (a textimmanent procedure). Their respective approaches of using the text of John's Gospel (JG) as a window and as a mirror are correlated. An analysis of the narrator's commentary (footnotes, asides) furnished important conclusions. They are that a referential correlation exists between the worlds within and outside the text. The direction of reference runs from the textexternal to the textexternal worlds, furthermore, the pragmatics of JG as a religio-historical text justifies the assumption that the readers/church within and outside the text are to be identified as ambivalent entities consisting of both Jewish and Hellenistic elements.